2022
DOI: 10.1093/bib/bbac375
|View full text |Cite
|
Sign up to set email alerts
|

PEcnv: accurate and efficient detection of copy number variations of various lengths

Abstract: Copy number variation (CNV) is a class of key biomarkers in many complex traits and diseases. Detecting CNV from sequencing data is a substantial bioinformatics problem and a standard requirement in clinical practice. Although many proposed CNV detection approaches exist, the core statistical model at their foundation is weakened by two critical computational issues: (i) identifying the optimal setting on the sliding window and (ii) correcting for bias and noise. We designed a statistical process model to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Taking CNV detection as an example, the size of sliding window is the crucial factor impacting the detection precision. Xuwen et al (56) have presented a CNV caller with a dynamic sliding window that automatically adjust the window size based on the length of CNV to achieve the optimal setting. The adaptive window with self-adopted size makes it capable of handling CNVs with various lengths ranging from kb-scale to chromosomearm level.…”
Section: Developing Novel Bioinformatics Tools With Error Controlmentioning
confidence: 99%
“…Taking CNV detection as an example, the size of sliding window is the crucial factor impacting the detection precision. Xuwen et al (56) have presented a CNV caller with a dynamic sliding window that automatically adjust the window size based on the length of CNV to achieve the optimal setting. The adaptive window with self-adopted size makes it capable of handling CNVs with various lengths ranging from kb-scale to chromosomearm level.…”
Section: Developing Novel Bioinformatics Tools With Error Controlmentioning
confidence: 99%
“…It can also find several other forms of gene structural variants. PEcnv [ 18 ] fills the gap in the recognition of small CNVs by detecting CNVs of varying sizes using a base coverage corrected model and a dynamic sliding window. IhybCNV [ 19 ] improves detection performance by integrating results from different detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Though this method has been widely used for signal processing, no study has reported its application in CNV peak detection and analysis. Currently, some of popular methods for detecting and analyzing CNVs include, but is not limited to, CNVkit [22], Control-FREEC [23], iCopyDAV [24], PEcnv [25] and CNV_IFTV [26]. Each of these methods has its own characteristics and advantages.…”
Section: Introductionmentioning
confidence: 99%